Tantangan dan Metode dalam Menerapkan Konsep Pendidikan Akhlak Perspektif Al-Ghazali di Era Modernisaasi Terhadap Generasi Milenial - Moh. Faizin; Wahyu Puspita Sari; Nadya Wahyu Pramita; Salsabila Faruq (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to describe the challenges and strategies that can be implemented in applying the concept of Islamic education from Al-Ghazali's perspective to the Millennial Generation. The research method is literature study (library), data obtained from books, journals, and articles published online. Data collection techniques by analyzing documentation and by analyzing documents that are relevant to this research. The data analysis technique in this study is descriptive qualitative analysis. The results in this study indicate that there are challenges faced by the millennial generation in the modernization era. First, the fading of good manners, both on social media and in the neighborhood. Second, disgraceful behavior began to be considered reasonable. Third, neglect worship. There are methods that can minimize these challenges by implementing Islamic education from Al-Ghazali's perspective. 1) Method by way of giving punishment, 2) Methods by giving rewards or gifts. Each method which is an educational tool can be applied in today's modernization era.